2021
DOI: 10.3390/microorganisms10010086
|View full text |Cite
|
Sign up to set email alerts
|

The Campylobacter jejuni Response Regulator and Cyclic-Di-GMP Binding CbrR Is a Novel Regulator of Flagellar Motility

Abstract: A leading cause of bacterial gastroenteritis, Campylobacter jejuni is also associated with broad sequelae, including extragastrointestinal conditions such as reactive arthritis and Guillain-Barré Syndrome (GBS). CbrR is a C. jejuni response regulator that is annotated as a diguanylate cyclase (DGC), an enzyme that catalyzes the synthesis of c-di-GMP, a universal bacterial second messenger, from GTP. In C. jejuni DRH212, we constructed an unmarked deletion mutant, cbrR−, and complemented mutant, cbrR+. Motility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 91 publications
2
11
1
Order By: Relevance
“…The expression of genes involved in chemotactic motility and quorum sensing in C.jejuni 11168-O ( cheA , tlp6 , tlp8 and luxS ) were examined in the presence and absence of ex-c-di-GMP by RT-PCR. CbrR gene as the only gene in the C. jejuni genome encoding GGDEF-like motif, reported to be potentially involved in c-di-GMP synthesis [ 48 ] was also included. The expression of, tlp6 , LuxS and CheA was upregulated in presence of 200 µM ex-c-di-GMP by 1.9 to 3-fold ( Figure 7 ); however, no significant effect on the expression of tlp8 was observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of genes involved in chemotactic motility and quorum sensing in C.jejuni 11168-O ( cheA , tlp6 , tlp8 and luxS ) were examined in the presence and absence of ex-c-di-GMP by RT-PCR. CbrR gene as the only gene in the C. jejuni genome encoding GGDEF-like motif, reported to be potentially involved in c-di-GMP synthesis [ 48 ] was also included. The expression of, tlp6 , LuxS and CheA was upregulated in presence of 200 µM ex-c-di-GMP by 1.9 to 3-fold ( Figure 7 ); however, no significant effect on the expression of tlp8 was observed.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of bacteria to auto-aggregate was assessed as described by [ 21 , 48 ]. Briefly, C. jejuni cells were harvested from overnight MHA plates, washed with PBS and resuspended in PBS to OD 600 0.8.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium deoxycholate resistance, flagellum biosynthesis, biofilm formation, chemotaxis (Raphael et al, 2005;Parrish et al, 2007;Cox et al, 2022) CheY (cj1118c) Chemotaxis (Lertsethtakarn et al, 2011;Zautner et al, 2012) CheA (cj0284c) Chemotaxis (Lertsethtakarn et al, 2011;Zautner et al, 2012) essential for H. pylori motility (Spohn and Scarlato, 1999;McDaniel et al, 2001;Brahmachary et al, 2004). The internal signal sensed by FlgS that triggers its autophosphorylation and subsequent activation of FlgR remains unknown (Alvarado et al, 2019).…”
Section: H Pylorimentioning
confidence: 99%
“…A second C. jejuni orphan RR, the protein CbrR, is an atypical RR that lacks a DNA-binding domain, but contains a C-terminal GGDEF motif commonly observed in diguanylate cyclase enzymes ( Raphael et al., 2005 ; Cox et al., 2022 ). Deletion mutants of CbrR exhibited increased sensitivity to sodium deoxycholate, enhanced motility and reduced ability to colonize chickens ( Raphael et al., 2005 ; Cox et al., 2022 ), whereas CbrR overexpression resulted in loss of flagella and a significant reduction in biofilm formation ( Cox et al., 2022 ). Yeast two-hybrid screenings have showed that CbrR interacts with CheA ( Parrish et al., 2007 ), which seems to indicate a putative role in chemotaxis.…”
Section: Structural and Functional Diversity Of Tcrs In H P...mentioning
confidence: 99%